Morphodynamics of an eroding beach and foredune in the Mekong River delta: Implications for deltaic shoreline change. (1st September 2017) - Anthony, E.J.; Dussouillez, P.; Dolique, F.; Besset, M.; Brunier, G.; Nguyen, V.L.; Goichot, M.
Abstract: River delta shorelines composed of sand may be characterized by complex spatial and temporal patterns of erosion and accretion even when sand supply is readily available. This is especially the case for deltas with multiple mouths subject to significant wave and tide influence. High-resolution topographical and wave and current measurements were conducted from 2010 to 2012 at Ba Dông beach, a popular resort located on the largest of the multiple inter-distributary plains of the Mekong River delta. Ba Dông beach is a mesotidal, multiple bar-trough system. The upper beach corresponds to the current active beach ridge in the sequence of ridges that have marked the progradation of the inter-distributary delta plains, and is capped by a low foredune that protects villages and agricultural land from marine flooding. During the low river-flow season, the beach is characterized by Northeast monsoon waves and strong longshore currents that transport sediment towards the southwest. Weaker longshore currents towards the northeast are generated by Southwest monsoon waves during the high river-flow season. Ba Dông beach underwent strong erosion between 2010 and 2012, following a phase of massive accretion. In 2012, this erosion resulted in breaching of the foredune, contributing to concerns that the Mekong delta had become vulnerable to retreat. The local erosion at Ba Dông needs to be considered, however, in the broader context of delta shoreline morphodynamics, which involves space- and time-varying patterns of beach accretion and erosion. These patterns are the present expressions of plan-view beach-ridge morphology in the delta, which is characterized by flaring and truncations that reflect changing beach morphodynamics in the course of deltaic progradation. We surmise that these patterns are related to complex interactions involving river water and sediment discharge, waves and wave-generated longshore currents, tidal currents, and shoreline orientation. Highlights: The Mekong delta shoreline shows alongshore variations in morphology and dynamics. Space-time-varying erosion/accretion affects Mekong delta-mouth beaches and foredunes. Beach/foredune erosion/accretion is intrinsic to Mekong delta shoreline evolution. Erosion/accretion is associated with bi-directional but SW-dominant sand transport. Erosion/accretion is the present expression of beach-ridge growth/flaring/truncation.